2022
DOI: 10.3390/cryst12081042
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of Water in Orthoclase Crystal and Its Implications for Feldspar Alteration

Abstract: The phenomenon of feldspar alteration that occurs in the interior of feldspar crystals remains poorly understood. We observed experimentally that water can go into orthoclase crystals under pressures of up to 600 MPa at room temperature. With increasing pressure, the FTIR spectra of colorless orthoclase show a sharp increase in integral absorbance from 1.50 cm−1 to 14.54 cm−1 and normalized integral absorbance from 120 cm−2 to 1570 cm−2; the pink orthoclase saturates quickly with no significant change in eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Using FTIR, Zuo et al [8] have found the presence of H 2 O molecules in the crystal structure of alkali feldspar within channels with preferable (001) orientation. It is suggested that this water plays an important role in the mechanisms of feldspar alteration and water preservation in nominally anhydrous minerals in Earth's depths.…”
Section: Crystal Chemistry and Properties Of Minerals And Their Synth...mentioning
confidence: 99%
“…Using FTIR, Zuo et al [8] have found the presence of H 2 O molecules in the crystal structure of alkali feldspar within channels with preferable (001) orientation. It is suggested that this water plays an important role in the mechanisms of feldspar alteration and water preservation in nominally anhydrous minerals in Earth's depths.…”
Section: Crystal Chemistry and Properties Of Minerals And Their Synth...mentioning
confidence: 99%
“…The translocation process is directly influenced by the both vertical and lateral water movements in the soils located on a slope. Among the multitude of the mineral skeleton grains of the soils, the feldspars are also present, being affected by the sericitization process, a very common hydrothermal alteration (Zuo et al, 2016;Zuo et al, 2022) and also an ubiquitous characteristic (Verati and Jourdan, 2014;Zuo et al, 2022). In the soils, the shrink and swell processes generated micro-shearing and consequently the reorganization of the clay domains with the striated b-fabric formation (Mermut et al, 1988) which are micromorphological features specific to vertic materials (very rich in clay).…”
Section: Introductionmentioning
confidence: 99%
“…Potassium feldspar has been widely studied as a potential potash fertilizer resource [ 6 , 7 , 8 ]. It may be alternated by water in some conditions [ 9 ] and used to produce multiphase slow-release fertilizers by sintering reaction [ 10 ].…”
Section: Introductionmentioning
confidence: 99%